2016
DOI: 10.1002/2015jb012238
|View full text |Cite
|
Sign up to set email alerts
|

Far‐field stress dependency of the failure mode of damage‐zone fractures in fault zones: Results from laboratory tests and field observations of siliceous mudstone

Abstract: The macroscopic failure mode (tensile/hybrid/shear) of damage‐zone fractures in fault zones may influence the hydrogeological properties of the fault zone. Application of the Griffith‐Coulomb failure criterion, combined with the simple assumption that failures are predominantly induced by an increase in differential stresses and/or a decrease in effective normal stresses resulting from stress concentrations generated at the asperities/tips of faults, suggests that (1) only tensile fractures propagate from faul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 88 publications
(159 reference statements)
2
14
0
Order By: Relevance
“…This is accompanied by dilatancy and by microfracturing of the original fabric but also by progressive decrease in porosity and pore size in the gouge with the nonclay particles embedded in reworked clay. The structure of macro-scale fracture in the samples compares well with Ishii et al (2011Ishii et al ( , 2016.…”
Section: Deformation Mechanismsmentioning
confidence: 81%
“…This is accompanied by dilatancy and by microfracturing of the original fabric but also by progressive decrease in porosity and pore size in the gouge with the nonclay particles embedded in reworked clay. The structure of macro-scale fracture in the samples compares well with Ishii et al (2011Ishii et al ( , 2016.…”
Section: Deformation Mechanismsmentioning
confidence: 81%
“…In addition, the hydraulic connectivity of fractures is not necessarily uniform across a formation. Ishii et al () and Ishii () indicated that fracture‐connectivity varies within the formation, depending on depth and the ductility index (DI). The DI is defined as follows (Ishii, ): DI =σnormalm/σnormalt σnormalm= (σ1+σ3)/2 p where σ ′ m is the effective mean stress (MPa), σ t is the tensile strength (MPa) of intact rock, σ 1 is the maximum principal stress (MPa), σ 3 is the minimum principal stress (MPa), and p is the pore pressure (MPa) of the rock mass.…”
Section: Introductionmentioning
confidence: 99%
“…The DI is defined as follows (Ishii, ): DI =σnormalm/σnormalt σnormalm= (σ1+σ3)/2 p where σ ′ m is the effective mean stress (MPa), σ t is the tensile strength (MPa) of intact rock, σ 1 is the maximum principal stress (MPa), σ 3 is the minimum principal stress (MPa), and p is the pore pressure (MPa) of the rock mass. Based on the Griffith‐Coulomb failure criterion, laboratory experiments, and core logging, Ishii () reported that tensile/hybrid (dilational) fractures tend to develop along faults during fault movement when DI < 2, while shear failure suppresses the formation of tensile/hybrid fractures when DI > 2 (Figure ). Such tensile/hybrid fractures, or brecciated zones that originate from numerous tensile/hybrid fractures, may act as highly conductive features (Aydin, ; Dholakia et al, ; Holland et al, ; Mazurek et al, ; Sibson, ; Tokiwa et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations